Atividades acadêmico-científico-culturais nos cursos de licenciatura em matemática da UNESP: estratégia de disputa no campo - Rodrigues, Vânia Cristina da Silva (2019)
In the last decades, there were several national and international research on the teacher education model. Many educators, including mathematical educators, looked into the subject of the formation of the elementary school math teacher looking for debating the necessary knowledge to teaching practice. In this sense, there were also changes in Brazilian legislation through the promulgation of guidelines for the training of basic teachers' formation, a factor that promoted changes in undergraduate courses to improve teaching in the country. Among these changes, we highlight the inclusion of Academic-Scientific-Cultural Activities (AACC) in undergraduate courses, as a way to promote the expansion of the cultural repertory of future teachers. With a minimum workload of 200 hours, AACC is an open curriculum space, set into a group of activities that can be chosen and developed by students during their training course. These activities purpose is enriching students' education with a stock of extracurricular knowledge for joining in scientific events, appointments, and monitoring, scientific initiation, artistic and cultural activities, among others. Each institution and course are allowed to deliberate on these activities for students' formation and how credits should apply for. Referring studies on teacher education and guidelines for teacher education, this research takes Mathematics Degree to the following interrogations: how is the proposal for insertion of the AACC contemplated in a mathematics degree courses at a public university in São Paulo state? Did these activities achieve the proposed goals? What assumptions have guided the development of these activities? Thus, the goal is presenting interpretations for the development of these activities in these courses using Bourdieu's theory as a reference. Thus, the work aims to analyze the development of AACC in mathematics degree courses of a public university in the State of São Paulo, aiming to understand their assumptions, practices and tensions in the academic field. This is a research of a quali-quantitative nature, in order to achieve the proposed objective were adopted as methodological procedures: bibliographic research in texts, documents and reports of the courses involved, but also the perception of coordinators and graduates of the courses analyzed. The sociological investigation carried out through the notion of mathematics field, allowed to interpret for the AACC, in the undergraduate courses in Mathematics of Unesp, as a space of the curriculum of reproduction and imprint of the mathematician habitus. According to the documents constituted in this work, these activities legitimize a certain kind of cultural capital. This cultural capital is related to knowledge activities relevant to the field of mathematics, prizing academic mathematics over the social and cultural background of the future mathematics teacher. It is about valuing a way of seeing and doing specific mathematics that, by keeping itself away from the teaching practice, does not address the specificities and does not meet the needs of the teacher's work and the proposed in the legal documents.